Nuclear kinematics in nearby AGN – I. An ALMA perspective on the morphology and kinematics of the molecular CO(2–1) emission. Issue 1 (4th May 2019) - Ramakrishnan, V; Nagar, N M; Finlez, C; Storchi-Bergmann, T; Slater, R; Schnorr-Müller, A; Riffel, R A; Mundell, C G; Robinson, A
Abstract: We present the molecular gas morphology and kinematics of seven nearby Seyfert galaxies obtained from our 230 GHz ALMA observations. The CO J = 2−1 kinematics within the inner ∼30 arcsec (≲9 kpc) reveals rotation patterns that have been explored using the Bertola rotation model and a modified version of the Kinemetry package. The latter algorithm reveals various deviations from pure circular rotation in the inner kiloparsec of all seven galaxies, including kinematic twists, decoupled, and counter-rotating cores. A comparison of the global molecular gas and stellar kinematics shows overall agreement in the position angle of the major axis and the systemic velocity, but larger discrepancies in the disc inclination. The residual maps obtained with both the methods show the presence of non-circular motions in most of the galaxies. Despite its importance, a detailed interpretation of the physics responsible for non-circular motions will be discussed in a forthcoming work.